MANAJEMEN STRATEGI DALAM MENINGKATKAN DAYA SAING SD GMIT SE-KECAMATAN LOBALAIN, KABUPATEN ROTE NDAO - Marlen Angela Daik; Desty A Bekuliu; Yanty Yunita Erni Sole; Yakobus Adi Saingo; Nimrot Doke Para; Reiningsih Putry Taku Namah; Kristian isach (Jurnal Dedikasi Pendidikan, 2024)
The Decreasing of public interest about the underdeveloped GMIT schools resulting in a decrease of interest continuing education. GMIT schools think of strategic steps to increase the competitiveness of institutions their education. The purpose of this is to analyze the strategic management of GMIT Elementary School in Lobalain District which was conducted to increase the schools’ competitiveness. The method used in this study is a qualitative method with a descriptive approach. The subjects in this study consist of 18 respondents consisting of 1 Principal and 2 teachers from each GMIT Elementary School in Lobalain District. The data collection techniques used is observation, interviews and documentation. The data analysis techniques that used are Analysis Interactive which is divided into 4 parts, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that strategic management has been implemented by school principals according to the implementation stages strategic management, namely observation, strategy formulation/strategy planning, implementation strategy, evaluation and control or supervision. This is done according to the conditions in each school. Efforts to increase the competitiveness of GMIT Elementary School in Lobalain District carried out in the form of observations in the internal and external environment to find out the strengths and the weaknesses of schools, preparing short-term and long-term work programs, implementing work programs and conducting regular evaluations.